2013
DOI: 10.1371/journal.pone.0067038
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Idiopathic Premature Ventricular Contractions and Ventricular Tachycardias Originating from Right Ventricular Septum

Abstract: BackgroundIdiopathic premature ventricular contractions (PVCs) and ventricular tachycardias (IVTs) originating from the subtricuspid septum and near the His bundle have been reported. However, little is known about the prevalence, distribution, electrocardiographic characteristics and the efficacy of radiofrequency catheter ablation (RFCA) for the ventricular arrhythmias arising from the right ventricular (RV) septum. This study aimed to investigate electrocardiographic characteristics and effects of RFCA for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Several series reported a higher likelihood of abandoning attempts at ablation of parahisian PVCs due to the possibility of inducing AV block . In this particular patient, LBBB in sinus rhythm increases this concern.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Several series reported a higher likelihood of abandoning attempts at ablation of parahisian PVCs due to the possibility of inducing AV block . In this particular patient, LBBB in sinus rhythm increases this concern.…”
Section: Discussionmentioning
confidence: 86%
“…According to Enrique et al, the presence of a positive QRS in lead II with negative QRS in III is associated with particular RV anatomical locations, namely, the parahisian region in the majority of patients. Lian‐Pin et al proposed that the earlier precordial R‐wave transition (<V4) is more common in PVCs arising from the tricuspid valvular septum than the basal RV septum because the origin of VAs in the former was located in the more posterior portion of the RV. Finally, Briceño et al described exactly the same electrocardiographic characteristics we found in SPR VAs.…”
Section: Discussionmentioning
confidence: 99%
“…RV septal PVCs have been described by Lian‐Pin et al . in a case series of 29 patients . They found that all PVCs had an rS or QS pattern in lead V1 and an LBBB morphology.…”
Section: Discussionmentioning
confidence: 96%
“…It may be hard for the ablation catheter to reach the LA using the trans‐aortic approach (Figure 2E). Moreover, in the remaining two patients (9%) with an unsuccessful procedure, successful results could not be achieved even though a trans‐aortic approach was additionally performed 8 (Figure 2F). The trans‐aortic approach was not considered to be able to gain stronger support and contact force than the trans‐interatrial septal approach.…”
Section: Discussionmentioning
confidence: 99%
“…The trans-aortic approach was not considered to be able to gain stronger support and contact force than the trans-interatrial septal approach. Further, the remaining one patient (5%) underwent a successful procedure that could be achieved from a coronary sinus approach 6,8 (Figure 2E (Table 3). Especially, the high-density mapping catheter is the only directional high-density mapping catheter that cannot only identify the local electrical signals but also more importantly can capture…”
Section: Rfca Of Ma-pvcsmentioning
confidence: 99%